ANN Soft-sensing Technology of Wind Shear for Large Direct-drive Wind Turbine - LI Zhiyong; WANG Xin; WANG Dian; HUANG Guohang (Kongzhi Yu Xinxi Jishu)
Wind shear not only threatens the service lifetime of wind power generation equipment, but also causes power quality problems such as voltage flicker on grid-connected side. To solve the problem that wind shear is difficult to directly measured, this paper established a PMSG mathematical model of three-blade with wind shear, analyzed the fluctuations in wind shear and mechanism of fluctuation from mechanical side to electromagnetic side, and proposed an ANN based wind shear effect soft-sensing method for large wind power generation equipment. The method is on the basis of adaptive noise cancellation, to indirectly measure wind shear caused by input turbine speed and stator current. By adopting GH Bladed, the simulation results show that the proposed soft-sensing technology can observe and accurately quantify the output torque fluctuation in real time without additional sensor equipment which lays a scientific and effective foundation for relevant researches on online compensation and control of wind turbines.